If you sing me a lullaby I will sing you a song about war : exhibition report presented in partial fulfillment for the degree of Master of Maori Visual Art 2013 - Cocker, Catherine (Massey University, 2016)
I grew up in a crack between cultures that broadened briefly with the acceptance of mixed marriages only to shrink back into a more elaborate and toxic packaging ready for the free market. No apologies, no paradoxes, just blatant contradictions, and perfect copies, a world of simulated realties and parasitic realty’s, just like England’s Dickensian1 past, we wallow in squalor, conflicted, for what exactly are we buying into when we are buying, and who do we become? This exhibition report explores the thinking behind my Masters exhibition “if you sing me a lullaby I will sing you a song about war.” It is specifically about the English colonisation of the Highlands and the Pacific and relates directly to my own family story. It highlights the disconnecting effects of colonisation on the psyche of the individual and the wider ethnic groups.
Keywords: Cocker, Catherine; Criticism and interpretation; Colonization in art; Colonization; Islands of the Pacific; Highlands; Scotland; Hunga mahi toi; Taipūwhenuatanga